(untitled) (Patan Pragya, 2022)
The sociology of markets has been the vibrant fields in sociology in the agreement that markets are social structure, law and markets as social structures tend to expand over long periods of time so as to include more people or goods relationship. The structural expansion of markets results in economic and organizational growth, extensive social relationships firms, workers, suppliers, customers, and governments. But like in many sociological literatures, the theory is a rational choice theory diverse; all assume that individuals choose the best action according to personal identification functions. Political economy views the linkages between states, law, and markets and the historical emergence of systems of governance. The capitalist arrangements and their effects on various outcomes, including economic development, is a part and parcel of the sociology of markets. Their approaches emphasize how the connectedness of social actors affects their behavior. Network analysis is a technique for finding social structures in relation to power, resource dependence, cooptation, information and trust to explain the social structures that emerge from their analyses. The world is now terrorized by the corona virus (COVID-19) started in Wuhan, China on November 31, 2019, the corona poses a serious economic socio-cultural, political and global issues. In this chaology, view, firms try to control markets by using their size, the existing market order. The sociology of markets gives us tools to decide whether a particular set of social structures protects economic growth and competition. The Chinese government immediately revived the industry and began rapid production and its global exports.